Testing the effects of group-affirmation in active conflict: Ukrainians’ trust toward Russia - Chung, Eunbin; Pechenkina, Anna O. (PloS one, 2023)
How can states with a history of recent armed conflict trust one another? Political psychology offers two competing approaches to increase trust between the publics of different countries: appealing to an overarching, common identity above the national level vs. affirming a sense of national identity. This study aims to examine the scope conditions of group-affirmation effects on trust in active conflicts by testing which group-affirmation approach increases trust towards Russia among the Ukrainian public. Distrust between Ukraine and Russia aggravates security fears and limits hope for a meaningful resolution of the bloodiest armed conflict in Europe since 1994. Hostility levels have risen dramatically between the populations of Ukraine and Russia after the events of 2013–2015. The study employs a survey experiment (between-subjects design) to evaluate these competing approaches. The survey was fielded in late May-June 2020 by a reputable public opinion research firm, the Kyiv International Institute of Sociology (KIIS), based in Ukraine. The results suggest that in areas where conflict is salient, national identity affirmation can increase trust in subsamples that hold preexisting baseline levels of affinity toward the outgroup. When combined with the more anti-Russian Ukrainians however, this positive effect was cancelled out. In contrast, emphasis on an overarching, common ingroup identity did not raise trust in any subgroups. Examining the disparate effects of national identity affirmation in anti-Russian and pro-Russian regional subsamples helps specify the scope conditions of which group-affirmation can be most effective.